Aquaporins in Cancer Biology - Moon, Chul So; Moon, David; Kang, Sung Koo (Frontiers in Oncology, 2022)
Aquaporins (AQPs) are a family of transmembrane water channel proteins, which were initially characterized as novel protein family that play a vital role in transcellular and transepithelial water movement. Aquaporins AQP1, AQP2, AQP4, AQP5 and AQP8 are primarily water selective, whereas AQP3, AQP7, AQP9 and AQP10 (called ‘aqua-glyceroporins’) also transport glycerol and other small solutes. Recently, multiple reports have suggested that AQPs participate important role in cancer cell growth, migration, invasion, and angiogenesis, each of them is import in human carcinogenesis. Here we review recent data concerning the involvement of AQPs in tumor growth, angiogenesis, and metastasis in addition to expression profiles from various resected cancer samples, and further discussed about molecular mechanisms behind. Moreover, we discussed about potential role of AQPs during the development of genomic instability and a modeling which describes an integration of binding between AQPs with various SH3 domain binning adaptor molecules.